PEMBELAJARAN BAHASA INGGRIS MENGGUNAKAN MEDIA BATANG ES KRIM - Herlinda Dian Permana Ningsih (Jurnal Ilmiah Visi, 2012)
Learning English often becomes dull ang frightening for participants of Package B. This articels presents an alternative teaching methode using icecream sticks as instructional media which have proved successful to create a jouyful learning. This method was practiced in teaching the participants of Package B in UPTD SKB in May 2010 including 13 participants in the first application. The result shows that those method can significantly improve the reading comprehension and learning motivation of the participants to study English.